Business statistics using excel : A complete course in data analytics - Panneerselvam, R (London : Routledge India, 2024)
This book gives readers a hands-on understanding of Excel-assisted statistical techniques to take effective business decisions. It showcases applications of the tools and techniques of statistics for analysing business data from the domain of business statistics. The volume provides an exhaustive introduction to the application of statistics in solving business problems and implementing data analytics for effective decision making in all kinds of business situations around the world. With an emphasis on simplicity in presentation of concepts of statistical methods and associated Excel functions, the volume explores the implementation of Excel functions through well-defined sequences of steps. It covers an array of key topics which include Discussions on real-world problems, decision support systems, scope of business statistics, types, and steps of research; Introduction to Excel and its mathematical and preliminary statistical functions; usage of different types of average functions; mean, median, and mode functions; measures of variation; measures of skewness of Excel; In-depth discussions on probability distributions, sampling distributions, testing of hypothesis, chi-square test, non-parametric tests of Excel; Extensive coverage on correlation and covariance, forecasting, analysis of variance, charts in Excel; and Analysis of the concept of linear programming, problem formulations, and techniques of linear programming, followed by the application in Excel. Comprehensive in scope and simple in approach, this book will be key for students and researchers of business studies, business administration, economics, finance, commerce, data analytics/science, and computer science. This will also serve as useful guidebook for business executives and working professionals across the globe.
Includes Index
Keywords: Microsoft Excel; Commercial statistics; Data processing; Business intelligence